A new approach for noninvasive transdermal determination of blood uric acid levels - Ching CTS (Dove Medical Press, 2014)
Congo Tak-Shing Ching,1,2 Kok-Khun Yong,3 Yan-Dong Yao,4 Huan-Ting Shen,3 Shiu-Man Hsieh,5 Deng-Yun Jheng,1 Tai-Ping Sun,1,6 Hsiu-Li Shieh11Department of Electrical Engineering, National Chi Nan University, Nantou, 2Department of Photonics and Communication Engineering, Asia University, Taichung, 3Department of Internal Medicine, Puli Christian Hospital, Nantou, People’s Republic of China; 4Division of Science and Technology, Hong Kong Community College, Hong Kong; 5Department of Orthopedic Surgery, Puli Christian Hospital, 6Department of Electronic Engineering, Nan Kai University of Technology, Nantou, People’s Republic of ChinaAbstract: The aims of this study were to investigate the most effective combination of physical forces from laser, electroporation, and reverse iontophoresis for noninvasive transdermal extraction of uric acid, and to develop a highly sensitive uric acid biosensor (UAB) for quantifying the uric acid extracted. It is believed that the combination of these physical forces has additional benefits for extraction of molecules other than uric acid from human skin. A diffusion cell with porcine skin was used to investigate the most effective combination of these physical forces. UABs coated with ZnO2 nanoparticles and constructed in an array configuration were developed in this study. The results showed that a combination of laser (0.7 W), electroporation (100 V/cm2), and reverse iontophoresis (0.5 mA/cm2) was the most effective and significantly enhanced transdermal extraction of uric acid. A custom-designed UAB coated with ZnO2 nanoparticles and constructed in a 1×3 array configuration (UAB-1×3-ZnO2) demonstrated enough sensitivity (9.4 µA/mM) for quantifying uric acid extracted by the combined physical forces of laser, electroporation, and RI. A good linear relationship (R2=0.894) was demonstrated to exist between the concentration of uric acid (0.2–0.8 mM) inside the diffusion cell and the current response of the UAB-1×3-ZnO2. In conclusion, a new approach to noninvasive transdermal extraction and quantification of uric acid has been established.Keywords: laser, electroporation, reverse iontophoresis, noninvasive, uric acid, biosensor